PENGENALAN KOMPUTER DAN PERSIAPAN ANBK UNTUK SISWA SDN CIHERANG 1 - Suarlembit, Yeremias A.; Suwandana, Avan; Sihite, Jelita D. S. L.; Wijaya, Ida Bagus R. L. P.; Mahyusa, Muhammad D.; Dewi, Fransisca I. R. (Jurnal Serina Abdimas, 2023)
Educational institutions are one of the institutions that are strongly supported by the presence of computers and devices. This encourages educational institutions to teach students from an early age, especially in rural areas, about computer devices including their functions and how to operate them. The PKM team found that a number of elementary schools in Ciherang Village, Cianjur Regency in West Java, specifically at SDN Ciherang 1, still had very little knowledge and operation of computers. The reason is due to inadequate computer equipment facilities and human resources. This is a problem faced by SDN Ciherang 1, because currently the Ministry of Education and Culture is implementing school assessment or evaluation through computer-based tests or surveys called computer-based national assessments (ANBK). ANBK activities are a substitute for the National Examination (UN) which requires students to be able to operate a computer. One of the schools that still lacks the introduction of computers is SDN Ciherang 1 in Cianjur Regency, where there is still a lack of computer facilities and human resources to guide students to carry out ANBK simulations. To overcome this, the PKM team developed a computer introduction and ANBK preparation program. The method of implementing the program is: first, socializing the introduction of computers, the target of this program is for students in grades 4 and 5 with the aim of students understanding how to operate a computer or laptop properly and correctly. Second, introducing ANBK, this is done by providing ANBK material and discussing examples of ANBK questions and providing guidance to students when taking part in ANBK activities. Third, hold a simulation test for ANBK activities, where this activity is an ANBK simulation test which will be given specifically to class 5 so that they can see and measure the extent of their ability to operate a computer and fill out the ANBK. The results of this program activity show that most students can operate a computer by typing sentences well, but a small number of students do not know what ANBK is and 3 students got the best scores when taking the ANBK simulation test. Lembaga Pendidikan merupakan salah satu lembaga yang sangat didukung keberadaan komputer dan perangkatnya. Hal ini mendorong lembaga pendidikan harus mengajarkan kepada siswa sejak dini, khususnya di daerah pedesaan mengenai perangkat komputer termasuk fungsi dan cara pengoperasian. Tim PKM menemukan sejumlah sekolah dasar di Desa Ciherang Kabupaten Cianjur di Jawa Barat, tepatnya di SDN Ciherang 1 masih sangat minim dalam hal pengetahuan dan pengoperasian komputer. Penyebabnya karena fasilitas perangkat komputer dan sumber daya manusia yang kurang memadai. Hal ini menjadi masalah yang dihadapi SDN Ciherang 1, karena saat ini Kemendikbud menerapkan penilaian atau evaluasi sekolah melalui tes atau survei berbasis komputer yang disebut dengan asesmen nasional berbasis komputer (ANBK). Kegiatan ANBK merupakan pengganti Ujian Nasional (UN) yang mengharuskan siswa untuk bisa mengoperasikan komputer. Salah satu sekolah yang masih minim dalam hal pengenalan komputer adalah SDN Ciherang 1 di Kabupaten Cianjur, dimana masih kekurangan fasilitas komputer dan SDM dalam membimbing siswa untuk melakukan simulasi ANBK. Untuk mengatasi hal itu tim PKM menyusun program pengenalan komputer dan persiapan ANBK. Metode pelaksanaan program yaitu: pertama, sosialisasi pengenalan komputer, target program ini untuk siswa kelas 4 dan 5 dengan tujuan siswa memahami cara pengoperasian komputer atau laptop dengan baik dan benar. Kedua, pengenalan ANBK, ini dilakukan dengan cara memberikan materi ANBK dan membahas contoh soal ANBK dan memberikan bimbingan kepada siswa ketika mengikuti kegiatan ANBK. Ketiga mengadakan test simulasi kegiatan ANBK dimana kegiatan ini merupakan sebuah test simulasi ANBK yang akan diberikan khusus kepada kelas 5 agar dapat melihat dan mengukur sampai dimana kemampuan mereka dalam mengoperasikan komputer dan mengisi ANBK. Hasil dari kegiatan program ini, menunjukkan bahwa Sebagian besar siswa dapat mengoperasikan komputer dengan mengetik kalimat dengan baik namun Sebagian kecil siswa belum mengetahui apa itu ANBK dan 3 siswa mendapatkan nilai terbaik saat mengikuti test simulasi ANBK.